Glenn's urologic surgery - Keane, Thomas E.; Graham, Sam D., Jr; Goldstein, Marc (Lippincott Williams & Wilkins/Wolters Kluwer, 2016)
"This textbook focuses on surgical procedures. Chapters are heavily illustrated and progress from Diagnosis to Indications for Surgery, to brief sections on Alternative Therapies, and then to detailed sections on surgical technique before closing with a discussion of outcomes as found in the literature. Each section opens with a thoroughly illustrated description of relevant anatomy"--Publisher's description.